2008
DOI: 10.1016/j.anbehav.2007.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Perception of food amounts by chimpanzees based on the number, size, contour length and visibility of items

Abstract: Nonhuman animals reliably select the largest of two or more sets of discrete items, particularly if those items are food items. However, many studies of these numerousness judgments fail to control for confounds between amount of food e.g., mass or volume) and number of food items. Stimulus dimensions other than number of items also may play a role in how animals perceive sets and make choices. Four chimpanzees (Pan troglodytes) completed a variety of tasks that involved comparisons of food items (graham crack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
86
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 45 publications
8
86
1
Order By: Relevance
“…Hence, we could hypothesize an advantage for the individual that detects and consumes the largest prey first. As suggested in other species [2,5], natural selection might have favoured decision mechanisms that prioritize the search for larger prey instead of the search for patches containing more overall prey.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, we could hypothesize an advantage for the individual that detects and consumes the largest prey first. As suggested in other species [2,5], natural selection might have favoured decision mechanisms that prioritize the search for larger prey instead of the search for patches containing more overall prey.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no reason to believe that the selective pressures in favour of the ability to estimate different quantities should not have acted on this vertebrate group. To fill this gap, we investigated quantitative abilities in ruin lizards (Podarcis sicula) using the most common procedure adopted in this field, a free choice test in the presence of food items differing in quantity [2][3][4][5]9]. In detail, in Experiment 1 we tested whether lizards attempt to maximize the amount of food intake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers in these fields have found that the ability to discriminate between different numbers of objects appears to be a foundational cognitive ability and have documented this ability in numerous species across the Animal Kingdom. For example, quantity discrimination has been demonstrated experimentally in several species of fish [5,11,[19][20][21], amphibians [8,22,23], birds [18,[24][25][26][27][28][29][30][31][32][33][34][35], mammals [9,[36][37][38][39][40][41], primates [42][43][44][45], human infants [46][47][48][49] and even some invertebrates [50][51][52]. The only study testing quantity discrimination in a reptile found that although ruin lizards (Podarcis sicula) do spontaneously select the larger quantity of food, they do not spontaneously select the option with a higher number of food items [53].…”
Section: Introductionmentioning
confidence: 99%
“…The primates are particularly well studied in these kinds of tests, and they accurately judge discrete quantities and continuous quantities (e.g. Boysen & Berntson 1995;Brannon & Terrace 2000;Hauser et al 2000;Beran & Beran 2004;Cantlon & Brannon 2006;Suda & Call 2006;vanMarle et al 2006;Hanus & Call 2007;Tomonaga 2007;Beran et al 2008a).…”
Section: Introductionmentioning
confidence: 99%